Qualidade sanitária da orla de João Pessoa-PB, com base fatores bióticos e abióticos - Nogueira, Elise Moraski (2018)
The Coastal Zone is a transitional environment between the continent, the sea and the atmosphere, which ensures food, protection against natural and anthropogenic disasters, housing and employment. However, due to its multiple uses, it also undergoes intense environmental degradation, mainly due to the process of disorderly occupation, extraction of natural resources and general pollution of soil, water and air. Water pollution mainly occurs through the untreated discharge of domestic and industrial effluents into streams, stormwater galleries, and directly into the sea, which can cause an accumulation of organic matter leading to an increase in the number of opportunistic microorganisms such as fungi and bacteria, in addition to potentially other organisms harmful to human health and other species. Balneability is a criterion for classification of water quality that uses physical and chemical parameters of water and the environment as well as biological indicators such as total coliforms. The investigation of balneability, the identification of the main degradation agents of the beaches and the composition of airborne fungi of the shore allowed diagnosing the sanitary quality of the urban beaches of João PessoaPB. As a result, Manaíra was the beach with the worst water quality, Penha was the one with the highest amount of organic and inorganic debris observed in the sand and Cabo Branco with the highest index of airborne fungi, mainly in the rainy season. As no relationship was found between water balneability and anemophilous fungi, it was concluded that this indicator cannot predict its presence, since even beaches considered to be primary contact recreation may contain potentially pathogenic microorganisms and therefore specific monitoring is required.